Care perspectives: Mothers of children with disabilities in a peri-urban setting in South Africa - Marcia A. Torres; Chioma O. Ohajunwa (African Journal of Disability)
Background: Within lower- to middle-income countries, mothers of children with disabilities often bear the burden of caregiving for their children, and experience various familial, systemic, structural and sociocultural challenges to the fulfilment of this role.